Implementasi Sistem Kontrol Motor Ac Berbasis Arduino Uno Pada Alat Ecosystem (Evaporatif Cooler System) - Rizki Sya'bani; Reni Rahmadewi; Dian Budi Santoso (Universitas Islam Lamongan, 2021)
Globalization era has a negative impact on the environment, one of which is affected by temperature. The condition of a hot room can cause an uncomfortable feeling to move in the room. The best room temperature for human comfort is 29°.ECOSYSTEM is an air conditioner that uses an indirect evaporative cooling system with control using Arduino uno and an application. This tool is made to cool the air in the room with the control of a cellphone. This research can be proven to be successful because the program code with the tool runs well. From the experiment it is also proven that when the speed increases, the current, watts, and RPM increase linearly.With this ECOSYSTEM tool, it is able to cool the room compared to a fan. Although the power generated is greater. Because the components used are different from conventional fans.